Uganda's response to sexual harassment in the public health sector: from "Dying Silently" to gender-transformational HRH policy - Constance Newman; Alice Nayebare; Stella Neema; Allan Agaba; Lilian Perry Akello (BMC, 2021)
Abstract Introduction Sexual harassment is a ubiquitous problem that prevents women's integration and retention in the workforce. Its prevalence had been documented in previous health sector studies in Uganda, indicating that it affected staffing shortages and absenteeism but was largely unreported. To respond, the Ministry of Health needed in-depth information on its employees' experiences of sexual harassment and non-reporting. Methods Original descriptive research was conducted in 2017 to identify the nature, contributors, dynamics and consequences of sexual harassment in public health sector workplaces and assess these in relation to available theories. Multiple qualitative techniques were employed to describe experiences of workplace sexual harassment in health employees' own voices. Initial data collection involved document reviews to understand the policy environment, same-sex focus group discussions, key informant interviews and baseline documentation. A second phase included mixed-sex focus group discussions, in-depth interviews and follow up key informant interviews to deepen and confirm understandings. Results A pattern emerged of men in higher-status positions abusing power to coerce sex from female employees throughout the employment cycle. Rewards and sanctions were levied through informal management/ supervision practices requiring compliance with sexual demands or work-related reprisals for refusal. Abuse of organizational power reinforced vertical segregation, impeded women's productive work and abridged their professional opportunities. Unwanted sexual attention including non-consensual touching, bullying and objectification added to distress. Gender harassment which included verbal abuse, insults and intimidation, with real or threatened retaliation, victim-blaming and gaslighting in the absence of organizational regulatory mechanisms all suppressed reporting. Sexual harassment and abuse of patients by employees emerged inadvertently. Discussion/conclusions Sex-based harassment was pervasive in Ugandan public health workplaces, corrupted management practices, silenced reporting and undermined the achievement of human resources goals, possibilities overlooked in technical discussions of support supervision and performance management. Harassment of both health system patients and employees appeared normative and similar to "sextortion." The mutually reinforcing intersections of sex-based harassment and vertical occupational segregation are related obstacles experienced by women seeking leadership positions. Health systems leaders should seek organizational and sectoral solutions to end sex-based harassment and make gender equality a human resource for health policy priority.